Higher body mass index is associated with worse hippocampal vasoreactivity to carbon dioxide - Glodzik, Lidia; Rusinek, Henry; Butler, Tracy; Li, Yi; Storey, Pippa; Sweeney, Elizabeth; Osorio, Ricardo S.; Biskaduros, Adrienne; Tanzi, Emily; Harvey, Patrick; Woldstad, Christopher; Maloney, Thomas; et al. (Frontiers in Aging Neuroscience, 2022)
Background and objectives Obesity is a risk factor for cognitive decline. Probable mechanisms involve inflammation and cerebrovascular dysfunction, leading to diminished cerebral blood flow (CBF) and cerebrovascular reactivity (CVR). The hippocampus, crucially involved in memory processing and thus relevant to many types of dementia, poses a challenge in studies of perfusion and CVR, due to its location, small size, and complex shape. We examined the relationships between body mass index (BMI) and hippocampal resting CBF and CVR to carbon dioxide (CVRCO2) in a group of cognitively normal middle-aged and older adults. Methods Our study was a retrospective analysis of prospectively collected data. Subjects were enrolled for studies assessing the role of hippocampal hemodynamics as a biomarker for AD among cognitively healthy elderly individuals (age > 50). Participants without cognitive impairment, stroke, and active substance abuse were recruited between January 2008 and November 2017 at the NYU Grossman School of Medicine, former Center for Brain Health. All subjects underwent medical, psychiatric, and neurological assessments, blood tests, and MRI examinations. To estimate CVR, we increased their carbon dioxide levels using a rebreathing protocol. Relationships between BMI and brain measures were tested using linear regression. Results Our group (n = 331) consisted of 60.4% women (age 68.8 ± 7.5 years; education 16.8 ± 2.2 years) and 39.6% men (age 70.4 ± 6.4 years; education 16.9 ± 2.4 years). Approximately 22% of them (n = 73) were obese. BMI was inversely associated with CVRCO2 (β = −0.12, unstandardized B = −0.06, 95% CI −0.11, −0.004). A similar relationship was observed after excluding subjects with diabetes and insulin resistance (β = −0.15, unstandardized B = −0.08, 95% CI −0.16, −0.000). In the entire group, BMI was more strongly related to hippocampal CVRCO2 in women (β = −0.20, unstandardized B = −0.08, 95% CI −0.13, −0.02). Discussion These findings lend support to the notion that obesity is a risk factor for hippocampal hemodynamic impairment and suggest targeting obesity as an important prevention strategy. Prospective studies assessing the effects of weight loss on brain hemodynamic measures and inflammation are warranted.